Peran Pinjaman Qardhul Hasan Dalam Meningkatkan Pendapatan Pelaku Usaha Mikro (Studi Kasus Di KOSPINMU Surya Mentari Karanganyar Kabupaten Pekalongan) - Cicih Kurniasih (2012115002) (Jurusan D-3 Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2018)
The problems discussed in this research is the role of loan qardhul hasan in improving income of micro businesses(case study on KospinMu Surya Mentari Karanganyar), the purpose of this study is to find out how the role of loan qardhul hasan in improving income micro businesses (case study on KospinMu Surya Mentari Karanganyar). This type of research is field research method using qualitative approach. The primary data is direct interviews with parties KospinMu Surya Mentari and direct interviews with micro entrepreneur, and the secondary data is library reference.Source of data obtained from documentation and interview. The Sampleused random sampling. Data analysis used qualitative descriptive analysis. This study concluded that the results of interviews with five respondents related the role of loan qardhul hasan in improving income of micro businesses (case study on KospinMu Surya Mentari Karanganyar), considered to be quite effective can be seen in the loan qardhul hasan 80% increased levels are rising, 20% stagnant in the sense its income remains and not increase. While the increase income has not increased significantly, this shows that there is still a lack of abillity to manage businesses due to lack of entrepreneurship training, strong competitive position, and not training for members who use the role of loan qardhul hasan Keywordss : qardhul hasan, income, micro business.